Dampak Kekerasan Seksual dalam Relasi Kuasa Akademisi: Analisis Berita Media dan Implikasi Futurologi - Maniah, Maniah; Kristanti Ayuanita (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The phenomenon of sexual violence in higher education has become an increasingly complex social issue, particularly when it occurs within power relations between lecturers and female students. This study aims to examine the psychological impacts experienced by victims of sexual violence in academic power relations and to project its long-term consequences through a futurological approach. Using a descriptive qualitative method and content analysis of five news reports from three national online media outlets (Media Indonesia, Detik.com, and Metrotvnews.com) published between 2020 and 2025, this research identifies media narrative patterns, the positioning of perpetrators and victims, and institutional responses to cases of sexual violence. The findings reveal that power imbalances, patriarchal culture, and weak institutional protection systems exacerbate victims’ conditions, leading to severe psychological trauma, fear, stigma, and feelings of helplessness. An analysis employing Michel Foucault’s theory of power relations, gender theory, and social futurology indicates that if left unaddressed, sexual violence in academic settings has the potential to create a long-term crisis of values and integrity. Therefore, systematic, preventive, and responsive efforts are essential to fostering a safe, equitable, and inclusive academic environment for all members of the academic community.